GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI PENGARUH ASIMETRI INFORMASI PADA MANAJEMEN LABA - Lestari, Sri Dewi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
In addition to improve the company's performance, one of the goals that’s needed to be achieved by all companies is to maximize profits gained. Profit is one of the most risky components as the basis for the decision making of its stakeholders. Earnings information has a very important role as a signal of the company's performance to meet a wide range of important decisions by users of information. This study was conducted to determine the effect of information asymmetry on earnings management by using Good Corporate Governance as moderating variables. This research was conducted at the company following the CGPI score in a row from 2010-2013 and listed on the Indonesia Stock Exchange. The method which is used in this research is regression analysis moderation. Results from this study indicate that the information asymmetry positive effect on earnings management and corporate governance as a moderating variable is able to weaken the asymmetry of information on earnings management that occurred in company.
Keywords: good corporate governance, asymmetry of information, earnings management.